Para uma árvore genealógica museológica: o caso singular do Museu Machado de Castro - Duarte Manuel Freitas (Midas: Museus e Estudos Interdisciplinares)
This study aims not only to outline the “genetic past” of Museu Nacional de Machado de Castro (Coimbra), founded in 1911, but also to list its contribution, at various levels, in the creation of other museum spaces within the district it operates. Based on the analysis of the collected sources (written and iconographic), a discursive structure was established, which begins with a brief reflection on the birth and perishing of the museological phenomena (I – In Principio), followed by an understanding of the personalities involved (II – Ecce homo), with special emphasis on its founder and the first director – António Augusto Gonçalves (1848-1932) – without neglecting his role as an artist and heritage's protector. Subsequently, we will look for the institution's remote origins, from the study of three late 19th-century city museums (Museu Municipal de Arte e Indústrias; Museu do Instituto de Coimbra and the Tesouro da Sé), receiving the estate, the missional vectors and the know-how from them (III – Avorum). Then, the founding act of the MNMC (IV – Nativitate) is examined, emphasizing the new socio-political context defined by the then young Portuguese Republic and by the museological concepts signed by its founder. The contribution of Coimbra’s state museum in the creation and maintenance of two new museological spaces (Museu Monográfico de Conímbriga and the Museu Etnográfico de Coimbra) will also be demonstrated (V – Semina), presenting itself in the final considerations (VI – Peractio), in addition to the usual summary, a family tree of the object of study.